Computer-Aided Design and Manufacturing versus Conventional Surgical Planning for Head and Neck Reconstruction: A Systematic Review and Meta-Analysis. Issue 1 (1st June 2021) - Padilla, Pablo L.; Mericli, Alexander F.; Largo, Rene D.; Garvey, Patrick B.
Abstract : Background: Virtual surgical planning and computer-aided design/computer-aided manufacturing (CAD/CAM) for complex head and neck reconstruction has a number of cited advantages over conventional surgical planning, such as increased operative efficiency, fewer complications, improved osseous flap union, immediate osseointegrated dental implant placement, and superior functional and aesthetic outcomes. The authors performed a systematic review and meta-analysis of the available evidence on CAD/CAM maxillofacial reconstruction with the primary purpose of determining which approach is more efficacious. Methods: In accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a PubMed and Embase database search was performed to identify English-language, human-subject studies of CAD/CAM–assisted head and neck reconstruction. All comparative studies were included in a meta-analysis to identify differences in operative time, ischemia time, surgical-site occurrence, microvascular complication, and partial or total flap loss between the two groups. All included studies (comparative and noncomparative) were used in the systematic review, summarizing the various flap characteristics, technical nuances, and functional and aesthetic outcomes. Results: Twelve articles were included in the meta-analysis, representing 277 patients in the CAD/CAM group and 419 patients in the conventional group. CAD/CAM was associated with 65.3 fewer minutes of operating room time (95 percent CI, −72.7 to −57.9 minutes; p < 0.0001) and 34.8 fewer minutes of ischemia time (95 percent CI, −38 to −31.5 minutes; p < 0.0001). There were no significant differences in surgical-site occurrence, nonunion, flap loss, microvascular complications, or hardware-related complications. Conclusions: CAD/CAM is associated with shorter operating room and ischemia times. There are no significant differences in flap or hardware-related complications between CAD/CAM and conventional surgical planning.